2007
DOI: 10.1021/jp0741861
|View full text |Cite
|
Sign up to set email alerts
|

Inducing the Rotation of a Single Phenyl Ring with Tunneling Electrons

Abstract: We report on the electron induced intramolecular rotation of a single phenyl ring of an azobenzene derivative adsorbed on a Au(111) surface using a low-temperature scanning tunneling microscope (STM). By proper functionalization of each of the two azobenzene's phenyl rings with CN end groups, we are able to identify two distinct isomers at the metal surface corresponding to two possible alignments of the functional groups in the trans conformer. Tunneling electrons induce molecular motion and intramolecular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 32 publications
4
76
0
Order By: Relevance
“…Thus, the molecule returns to its original conformation with high probability, and conformational switching occurs rarely. Such low-quantum-yield switching has been observed in recent experiments [16,27,28]. For instance, STM measurements on azobenzene derivatives show that only one out of 10 10 tunneling electrons induces a switching event [16].…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, the molecule returns to its original conformation with high probability, and conformational switching occurs rarely. Such low-quantum-yield switching has been observed in recent experiments [16,27,28]. For instance, STM measurements on azobenzene derivatives show that only one out of 10 10 tunneling electrons induces a switching event [16].…”
mentioning
confidence: 69%
“…An essential requirement for electric circuits of nanoscale dimensions is a molecular device that can be switched between two distinct conductive states. Because of intrinsic bistabilities, many single-molecule junctions reveal switching behavior, e.g., involving cis and trans isomers of a molecule [15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…This is indicative of an instability of the imaged structure triggered by tunneling electrons. 3,12 To understand this behavior, the tunneling current was measured in open feedback loop conditions as a function of time. Current traces recorded in the fuzzy area show an oscillation between two values (see Figure 2a), which we label as low-and high-conductance state.…”
Section: -25mentioning
confidence: 99%
“…Surface-bounded molecular switches, rotors and motors are fascinating since they can be exposed to external stimuli [4][5][6] and investigated by surface analysis methods [7][8][9][10]. Recent studies have shown that surface-bounded molecular switches and rotors can be used in experimental techniques such as scanning tunneling microscopy and spectroscopy (STM/STS) which also allow the measurement of molecular switching/rotor rates and energy barriers [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%